Investigation of postoperative intraocular pressure in cases of silicone oil removal using 25-gauge transconjunctival sutureless vitrectomy with oblique incisions - Takashina, Hirotsugu (Clin Ophthalmol, 2015)
BACKGROUND: The purpose of this study was to investigate postoperative intraocular pressure (IOP) in cases of silicone oil (SO) removal when using 25-gauge transconjunctival sutureless vitrectomy (TSV) with oblique incisions. METHODS: We enrolled ten consecutive eyes with SO removal (SO group) and eleven consecutive eyes with idiopathic epiretinal membrane (ERM) as the initial vitrectomy (ERM group) in cases using 25-gauge TSV with oblique incisions. Postoperative IOPs were compared between the two groups at each of the four examination periods. RESULTS: No significant differences were identified in any of the periods examined. CONCLUSION: The use of 25-gauge TSV with oblique incisions resulted in almost equivalent postoperative IOPs between cases with SO removal and idiopathic ERM as the initial operation. Self-sealing sclerotomy in 25-gauge TSV with oblique incisions may primarily involve the valve architecture, and be complemented by vitreous incarceration.